Enhanced Susceptibility of Galectin-1 Deficient Mice to Experimental Colitis - Fernandez-Perez, Raquel; Lopez-Santalla, Mercedes; Sánchez-Domínguez, Rebeca; Alberquilla, Omaira; Gutiérrez-Cañas, Irene; Juarranz, Yasmina; Bueren, Juan A.; Garin, Marina I. (Frontiers in Immunology, 2021)
Galectin-1 is a β-galactoside‒binding lectin, ubiquitously expressed in stromal, epithelial and different subsets of immune cells. Galectin-1 is the prototype member of the galectin family which shares specificity for β-galactoside containing proteins and lipids. Immunomodulatory functions have been ascribed to endogenous galectin-1 due to its induction of T cell apoptosis, inhibitory effects of neutrophils and T cell trafficking. Several studies have demonstrated that administration of recombinant galectin-1 suppressed experimental colitis by modulating adaptive immune responses altering the fate and phenotype of T cells. However, the role of endogenous galectin-1 in intestinal inflammation is poorly defined. In the present study, the well-characterised acute dextran sulfate sodium (DSS)-induced model of ulcerative colitis was used to study the function of endogenous galectin-1 during the development of intestinal inflammation. We found that galectin-1 deficient mice (Lgals1−/− mice) displayed a more severe intestinal inflammation, characterized by significantly elevated clinical scores, than their wild type counterparts. The mechanisms underlying the enhanced inflammatory response in colitic Lgals1−/− mice involved an altered Th17/Th1 profile of effector CD4+ T cells. Furthermore, increased frequencies of Foxp3+CD4+ regulatory T cells in colon lamina propria in Lgals1−/− mice were found. Strikingly, the exacerbated intestinal inflammatory response observed in Lgals1-/-mice was alleviated by adoptive transfer of wild type Foxp3+CD4+ regulatory T cells at induction of colitis. Altogether, these data highlight the importance of endogenous galectin-1 as a novel determinant in regulating T cell reactivity during the development of intestinal inflammation.